1990
DOI: 10.1111/j.1745-4603.1990.tb00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Thermal Properties as Well as Network Microstructure and Rheology on Protein Concentration for Ovalbumin and Vicilin

Abstract: Critical protein concentration (CPC) values for network formation for ovalbumin (5.5%, w/w) and vicilin (8%, w/w) were determined based on the appearance of a well crosslinked network using light microscopy, in conjunction with a significant decrease in the dynamic rheological parameter, tan δ= G″/G′. Increasing protein concentration resulted in increased G′ (storage modulus) and G″ (loss modulus) for both proteins. These relationships were described by power law equations. Ovalbumin networks had a lower CPC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 31 publications
3
26
1
1
Order By: Relevance
“…NaCl has been described as a stabilizing salt by its ability to increase the thermal stability of plant proteins . However, in another study, NaCl at concentrations between 5.8 and 29.2 g/l was shown to cause a decrease in the enthalpy of denaturation of ovalbumin, indicative of protein denaturation (Arntfield, Murray, & Ismond, 1990). The general trend in ranking anions in terms of their ability to stabilize proteins depends on the protein in question.…”
Section: Resultsmentioning
confidence: 97%
“…NaCl has been described as a stabilizing salt by its ability to increase the thermal stability of plant proteins . However, in another study, NaCl at concentrations between 5.8 and 29.2 g/l was shown to cause a decrease in the enthalpy of denaturation of ovalbumin, indicative of protein denaturation (Arntfield, Murray, & Ismond, 1990). The general trend in ranking anions in terms of their ability to stabilize proteins depends on the protein in question.…”
Section: Resultsmentioning
confidence: 97%
“…The loss modulus (G″) that measures the viscous component of the developing 3D gel network rapidly increased during the cooling phase, which might be attributed to substantial H-bond and hydrophobic bond formation between protein strands. The increase in G′ and G′′ during cooling is generally ascribed to gel structure strengthening by attractive forces, such as van der Waals interactions and H-bonding between protein strands [21,34,35]. The unchanged moduli values for the CRUC homohexamer indicated that it has poor ability to form heatinduced gel networks (Fig.…”
Section: Heat-induced Gelationmentioning
confidence: 96%
“…The rheometer was equipped with 40 mm parallel (flat) plate geometry. Input strain amplitude for dynamic analysis was 0.02, a value found to be in the linear viscoelastic region in a previous study (Arntfield et al, 1990). This strain was used for all rheological measurements.…”
Section: Rheologymentioning
confidence: 99%
“…Rheological data (G 0 , G 00 and tan d) were collected every 0.5 min during the frequency sweep with a thermal equilibrium time of 10 s. Frequency sweeps of the final product were conducted over a range of 0.1-10 Hz at 25°C. Values at 1 Hz were recorded for comparison as has been done previously (Arntfield et al, 1990;Cai and Arntfield, 1997). Samples were run in duplicate.…”
Section: Rheologymentioning
confidence: 99%